Environment-friendly anti-wrinkle woven cloth as well as preparation method and application thereof
By interwoven polyester and linen yarns in the woven fabric and carrying out esterification and carbon dioxide in situ synthesis reactions, the problem of insufficient wrinkleability of the woven fabric is solved, and the wrinkle resistance and breathability are improved. It is suitable for the preparation of high-quality clothing and Decorative materials.
Patent Information
- Application Number
- CN202411577186.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing woven fabrics are prone to wrinkles due to their insufficient wrinkleness and water absorption. They need to be ironed regularly after wearing or washing, which makes them inconvenient to use and maintain.
Polyester yarn and linen yarn are interwoven into a composite base cloth, and the crosslinking bonds and calcium carbonate are formed through esterification treatment and carbon dioxide in situ synthesis reaction, thereby improving the wrinkle resistance and dimensional stability of the fiber.
It has achieved improved wrinkle resistance, breathability and wear resistance of woven fabrics, reduced wrinkle phenomenon, reduced fiber damage, and is suitable for the preparation of clothes and decorative materials.
Smart Images

Figure CN119287663A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite woven fabrics, and in particular to an environmentally friendly wrinkle-resistant woven fabric and a preparation method and application thereof. Background Art
[0002] Weaving has a history of more than 7,000 years in China. Ancient people used grass to weave clothes to keep warm. Currently, flax fiber is the most common choice for weaving. Flax fiber is strong, soft and fine, and is an important raw material for the textile industry.
[0003] Linen fabrics are prone to shrinkage and wrinkles after wearing or washing. Frequent ironing is required to keep them smooth, which is inconvenient in use and maintenance. Although the woven fabrics have enhanced structural stability due to the interweaving of warp and weft, they may also wrinkle in some cases due to their weaving and structural characteristics, especially after sitting or lying for a long time or folding and storing. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide an environmentally friendly wrinkle-resistant woven fabric and a preparation method and application thereof.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] In a first aspect, the present invention provides a method for preparing an environmentally friendly wrinkle-resistant woven fabric, comprising the following steps:
[0007] S1. Using polyester yarn and linen yarn as warp yarn and / or weft yarn respectively, and weaving the warp yarn and weft yarn perpendicular to each other to obtain a composite base fabric;
[0008] S2, immersing the composite base fabric in a first finishing agent, taking out the composite base fabric and curing it, washing and drying it after curing to obtain an esterified base fabric; wherein the mass density of the first finishing agent is 400 to 600 g·m -2 The first finishing agent is an ethanol solution of sodium hypophosphite and pyromellitic acid, with a pH of 2 to 6; sodium hypophosphite and pyromellitic acid account for 70 to 80 wt% of the total mass of the first finishing agent, the mass ratio of sodium hypophosphite to pyromellitic acid is a molar ratio of (0.5 to 1): 1, the curing temperature is 150 to 180 ° C, and the curing time is 30 to 120 s;
[0009] S3, immersing the esterified base fabric in a second finishing agent, which is a mixed solution of sulfonic acid type waterborne polyurethane, magnesium chloride and calcium hydroxide, and then placing the base fabric in a container filled with carbon dioxide gas, and continuing to introduce carbon dioxide gas into the container for an in-situ synthesis reaction for 15 to 30 minutes, so that calcium hydroxide reacts with carbon dioxide to generate calcium carbonate, taking out the base fabric after the reaction, drying it, and then washing it, and after drying, obtaining the environmentally friendly anti-wrinkle woven fabric; wherein the mass density of the second finishing agent is 100 to 200 g·m- 2 ; The sulfonic acid type water-based polyurethane, magnesium chloride and calcium hydroxide account for 60-70wt% of the total mass of the second finishing agent, and the mass ratio of the sulfonic acid type water-based polyurethane, magnesium chloride and calcium hydroxide is (20-30): (20-25): 1; the flow rate of the carbon dioxide gas introduced into the container is 200-300mL / min.
[0010] The present invention uses flax and polyester to make woven cloth. Flax fabric is famous for its good air permeability, which can keep the skin dry and comfortable; polyester has high strength and wrinkle resistance, and is not easy to wear or tear, but due to its symmetrical molecular structure and high crystallinity, it lacks hydrophilic groups, resulting in poor water absorption and dyeing properties, and because its fiber structure is relatively tight, it is not conducive to air circulation, which means that clothes made of polyester are not easy to wrinkle, but at the same time, it is not easy to absorb moisture, and sweat cannot evaporate to the outside world in time. Therefore, the fabric mixed with polyester and flax complements each other in fiber structure, so that the fabric has both the stiffness and wrinkle resistance of polyester and the air permeability of flax, which is more comfortable to wear. Although polyester has poor hygroscopicity, after the two are combined, the fabric can still maintain good air permeability, and with the help of the hygroscopicity of flax, the body can be kept dry.
[0011] The woven fabric of the present invention is woven from flax and polyester into a composite base fabric, and then the composite base fabric is firstly subjected to an esterification treatment, that is, the base fabric is immersed in an ethanol solution of sodium hypophosphite and pyromellitic acid. Pyromellitic acid is an aromatic carboxylic acid, and an esterification reaction occurs between the hydroxyl groups on cellulose in flax in the presence of a catalyst, sodium hypophosphite. The cross-linked bonds formed by the esterification can fix the relative positions between the fiber molecules, limit the deformation ability of the fibers, and make the flax more easily recover to its original state after being acted upon by an external force, thereby achieving an anti-wrinkle effect.
[0012] Since pyromellitic acid has poor water solubility, ethanol is selected as the solvent. The ortho-carboxyl group on pyromellitic acid can not only directly undergo esterification reaction with cellulose, but also dehydrate to form anhydride, which further reacts with cellulose. Moreover, the system pH is limited to 2-6 during the esterification process. Acidic conditions help promote the esterification reaction because the acid can act as a proton source to promote the protonation of the hydroxyl group, which is conducive to the attack of the nucleophilic agent hypophosphite on the carbonyl carbon. Specifically, the hypophosphite attacks the carbonyl functional group of the mixed anhydride to form an active intermediate state, and then undergoes a nucleophilic substitution reaction with the active hydroxyl functional group of cellulose to form cellulose ester. This process is more favorable under acidic conditions because the acidic environment helps to stabilize the intermediates and transition states in the reaction. Therefore, the cross-linking of pyromellitic acid and cellulose is mainly through direct esterification, rather than indirect esterification through anhydride intermediates, which reduces the loss of intermediates and the occurrence of side reactions, thereby improving the reaction efficiency and making the cross-linking process more efficient, which significantly improves the wrinkle resistance, water resistance, heat resistance, etc. of linen.
[0013] In addition, after the flax cellulose reacts with the polycarboxylic acid, the strength of the fiber will be lost, which is mainly due to the accumulation of damage to the macromolecular chains in the fiber. The esterification catalytic effect of pyromellitic acid is lower than that of aliphatic carboxylic acids (such as 1,2,3,4-butanetetracarboxylic acid and citric acid), so the present invention uses pyromellitic acid as a finishing agent to improve the anti-wrinkle effect of flax fiber while reducing the molecular damage of the fiber, that is, it can maintain good strength and air permeability.
[0014] The esterified base fabric is then immersed in a mixed solution (i.e., the second finishing agent) containing sulfonic acid type waterborne polyurethane, magnesium chloride and calcium hydroxide, and then carbon dioxide gas is introduced, that is, calcium carbonate is synthesized in situ on the base fabric, and the calcium carbonate can improve the anti-wrinkle effect of the base fabric. Although magnesium chloride and carbon dioxide can react to form magnesium carbonate under certain conditions, the reaction can only occur under alkaline conditions such as ammonia. Therefore, in this step, when carbon dioxide is introduced, carbon dioxide will preferentially react with calcium hydroxide. This is because calcium hydroxide is a strong base, and the reaction of the hydroxide ions in its solution with carbon dioxide is more favorable kinetically, and the resulting calcium carbonate precipitate is also thermodynamically stable. In addition, the isocyanate group (-NCO) in the polyurethane resin can also react with the unesterified hydroxyl group in cellulose to form covalent crosslinks, thereby improving the anti-wrinkle performance and dimensional stability of the fabric. When magnesium chloride is dissolved in water, it releases Mg 2+ Ions, which can be adsorbed on the surface of calcium carbonate particles. This adsorption can increase the positive charge on the surface of the particles, thereby increasing the repulsion between the particles, reducing the aggregation of the particles, and improving its dispersibility in the medium; and magnesium chloride can also act as a catalyst to accelerate the cross-linking reaction between polyurethane resin and fiber, shorten the curing time, and improve the finishing efficiency.
[0015] Preferably, in step S1, the flax yarn is warp yarn with a warp density of 200-250 yarns / inch; the polyester yarn is weft yarn with a weft density of 150-200 yarns / inch. Since the radial breaking strength of the fabric is generally higher than the weft strength, it is preferred to use polyester, which is a relatively strong raw material, as the weft yarn.
[0016] Preferably, in step S2, the curing temperature is 160-175° C. and the curing time is 60-90 seconds.
[0017] Preferably, in step S2, the composite base fabric is immersed in a first finishing agent, the composite base fabric is taken out, dried and then cured; the drying temperature is 90-100° C. and the drying time is 1-5 min.
[0018] Preferably, the sulfonic acid type waterborne polyurethane is at least one of PU2650, PU2660, PU2690 and PU2695.
[0019] Preferably, the pH of the first finishing agent is 2 to 3. In the reaction system of sodium hypophosphite, polycarboxylic acid and cellulose, the acidic condition not only affects the ionization and catalytic activity of sodium hypophosphite, but also promotes the activity of the carboxyl group in the polycarboxylic acid and the entire esterification reaction. After testing, the pH in the range of 2 to 3 can make the performance of the woven fabric better.
[0020] Preferably, in step S3, the flow rate of the carbon dioxide gas introduced into the container is 250-300 mL / min.
[0021] Preferably, in step S3, the drying temperature is 50-70° C. and the drying time is 5-10 min.
[0022] Preferably, in step S3, the mass ratio of sulfonic acid type waterborne polyurethane to magnesium chloride is (1.15-1.2):1.
[0023] In a second aspect, the present invention provides an environmentally friendly anti-wrinkle woven fabric, which is prepared by the preparation method of the environmentally friendly anti-wrinkle woven fabric.
[0024] In a third aspect, the present invention provides a use of an environmentally friendly wrinkle-resistant woven fabric in preparing decorative materials and / or clothing.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] After the woven fabric of the present invention weaves flax and polyester into a composite base fabric, the composite base fabric is first esterified, that is, the base fabric is immersed in an ethanol solution of sodium hypophosphite and pyromellitic acid, and the hydroxyl group on the cellulose in the flax reacts with the carboxyl group on the pyromellitic acid in the presence of the catalyst sodium hypophosphite to obtain an esterified base fabric, thereby achieving an anti-wrinkle effect; then the esterified base fabric is immersed in a mixed solution (i.e., a second finishing agent) comprising sulfonic acid type waterborne polyurethane, magnesium chloride and calcium hydroxide, and then carbon dioxide gas is introduced, that is, calcium carbonate is synthesized in situ on the base fabric, and the calcium carbonate can improve the anti-wrinkle effect of the base fabric, and at the same time, the isocyanate group (-NCO) in the polyurethane resin can react with the hydroxyl group in the cellulose to form a covalent bond crosslinking, thereby improving the anti-wrinkle performance and dimensional stability of the fabric, and magnesium chloride helps to enhance the dispersibility and stability of calcium carbonate in the base fabric, and can be used as a catalyst to accelerate the crosslinking reaction between the polyurethane resin and the fiber, shorten the curing time, and improve the finishing efficiency. Therefore, the woven fabric of the present invention has good anti-wrinkle performance, air permeability and wear resistance, and can be used to prepare clothes and decorative materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a physical picture of the woven cloth of the present invention. DETAILED DESCRIPTION
[0028] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0029] In the following examples and comparative examples, the sources of the raw materials used are as follows:
[0030] Linen yarn: manufacturer is Fujian Yiming Textile Co., Ltd., brand 24s ring-spun, 100% polyester;
[0031] Polyester yarn: manufacturer is Dongguan Huili Textile Raw Materials Co., Ltd., brand name is SFL03, yarn count is 26N / 2, ring spinning;
[0032] Sodium hypophosphite: The manufacturer is Changshu Xinte Chemical Co., Ltd.
[0033] Pyromellitic acid: The manufacturer is Boshan Hengtai Chemical Plant, purity ≥99%;
[0034] Sulfonic acid type waterborne polyurethane: manufacturer is Xiamen Aikema Chemical Co., Ltd., brand PU2650, PU2660, PU2695
[0035] Magnesium chloride: manufacturer is Shanghai Aladdin Biochemical Technology Co., Ltd., brand number is M113687;
[0036] Calcium hydroxide: The manufacturer is Shanghai McLean Biochemical Technology Co., Ltd., the brand number is C916711, and the purity is 90%.
[0037] Unless otherwise specified, other materials, reagents, etc. used in the examples and comparative examples can be obtained from commercial sources.
[0038] Example 1
[0039] A method for preparing an environmentally friendly wrinkle-resistant woven fabric comprises the following steps:
[0040] S1, using linen yarn as warp yarn with a warp density of 210 yarns / inch; using polyester yarn as weft yarn with a weft density of 185 yarns / inch, and weaving the warp yarn and the weft yarn perpendicular to each other to obtain a composite base fabric;
[0041] S2, immersing the composite base fabric in the first finishing agent, taking out the composite base fabric, drying it and then curing it; the drying temperature is 95°C and the time is 3 minutes. After taking out the composite base fabric, curing it, washing it and drying it after curing, to obtain an esterified base fabric; wherein the mass density of the first finishing agent is 500g·m -2 The first finishing agent is an ethanol solution of sodium hypophosphite and pyromellitic acid, with a pH of 3; sodium hypophosphite and pyromellitic acid account for 75wt% of the total mass of the first finishing agent, the mass ratio of sodium hypophosphite to pyromellitic acid is a molar ratio of 0.6:1, the curing temperature is 170°C, and the time is 60s;
[0042] S3, immersing the esterified base fabric in a second finishing agent, which is a mixed solution of sulfonic acid type waterborne polyurethane, magnesium chloride and calcium hydroxide, and then placing the base fabric in a container filled with carbon dioxide gas, and continuing to introduce carbon dioxide gas into the container for an in-situ synthesis reaction for 20 minutes, so that calcium hydroxide reacts with carbon dioxide to generate calcium carbonate, taking out the base fabric after the reaction, drying it at 60° C. for 8 minutes, and then washing it, and after drying, obtaining the environmentally friendly anti-wrinkle woven fabric;
[0043] The mass density of the second finishing agent is 100-200 g·m -2 The sulfonic acid waterborne polyurethane, magnesium chloride and calcium hydroxide account for 60-70wt% of the total mass of the second finishing agent, and the mass ratio of the sulfonic acid waterborne polyurethane, magnesium chloride and calcium hydroxide is 27:23:1. The sulfonic acid waterborne polyurethane is PU2650. The flow rate of the carbon dioxide gas introduced into the container is 250mL / min.
[0044] Example 2
[0045] A method for preparing an environmentally friendly wrinkle-resistant woven fabric comprises the following steps:
[0046] S1, using linen yarn as warp yarn with a warp density of 200 yarns / inch; using polyester yarn as weft yarn with a weft density of 150 yarns / inch, and weaving the warp yarn and the weft yarn perpendicular to each other to obtain a composite base fabric;
[0047] S2, immersing the composite base fabric in the first finishing agent, taking out the composite base fabric, drying it and then curing it; the drying temperature is 90°C and the time is 5 minutes. After taking out the composite base fabric, curing it, washing it and drying it after curing, to obtain an esterified base fabric; wherein the mass density of the first finishing agent is 400g·m -2 The first finishing agent is an ethanol solution of sodium hypophosphite and pyromellitic acid, with a pH of 2; sodium hypophosphite and pyromellitic acid account for 70wt% of the total mass of the first finishing agent, the mass ratio of sodium hypophosphite to pyromellitic acid is a molar ratio of 0.5:1, the curing temperature is 150°C, and the time is 120s;
[0048] S3, immersing the esterified base fabric in a second finishing agent, which is a mixed solution of sulfonic acid type waterborne polyurethane, magnesium chloride and calcium hydroxide, and then placing the base fabric in a container filled with carbon dioxide gas, and continuing to introduce carbon dioxide gas into the container for an in-situ synthesis reaction for 30 minutes, so that calcium hydroxide reacts with carbon dioxide to generate calcium carbonate, taking out the base fabric after the reaction, drying it at 50°C for 10 minutes, and then washing it. After drying, the environmentally friendly anti-wrinkle woven fabric is obtained; wherein the mass density of the second finishing agent is 100g·m -2 The sulfonic acid waterborne polyurethane, magnesium chloride and calcium hydroxide account for 60wt% of the total mass of the second finishing agent, and the mass ratio of the sulfonic acid waterborne polyurethane, magnesium chloride and calcium hydroxide is 20:20:1. The sulfonic acid waterborne polyurethane is PU2660. The flow rate of the carbon dioxide gas introduced into the container is 200mL / min.
[0049] Example 3
[0050] A method for preparing an environmentally friendly wrinkle-resistant woven fabric comprises the following steps:
[0051] S1, using linen yarn as warp yarn with a warp density of 250 yarns / inch; using polyester yarn as weft yarn with a weft density of 200 yarns / inch, and weaving the warp yarn and the weft yarn perpendicular to each other to obtain a composite base fabric;
[0052] S2, immersing the composite base fabric in the first finishing agent, taking out the composite base fabric, drying it and then curing it; the drying temperature is 100°C and the time is 1 min. After taking out the composite base fabric, curing it, washing it and drying it after curing, to obtain an esterified base fabric; wherein the mass density of the first finishing agent is 600g·m -2The first finishing agent is an ethanol solution of sodium hypophosphite and pyromellitic acid, with a pH of 6; sodium hypophosphite and pyromellitic acid account for 80wt% of the total mass of the first finishing agent, the mass ratio of sodium hypophosphite to pyromellitic acid is a molar ratio of 1:1, the curing temperature is 180°C, and the time is 30s;
[0053] S3, immersing the esterified base fabric in a second finishing agent, which is a mixed solution of sulfonic acid type waterborne polyurethane, magnesium chloride and calcium hydroxide, and then placing the base fabric in a container filled with carbon dioxide gas, and continuing to introduce carbon dioxide gas into the container for an in-situ synthesis reaction for 15 minutes, so that calcium hydroxide reacts with carbon dioxide to generate calcium carbonate, taking out the base fabric after the reaction, drying it at 70°C for 5 minutes, and then washing it. After drying, the environmentally friendly anti-wrinkle woven fabric is obtained; wherein the mass density of the second finishing agent is 200g·m -2 The sulfonic acid type waterborne polyurethane, magnesium chloride and calcium hydroxide account for 70wt% of the total mass of the second finishing agent, and the mass ratio of the sulfonic acid type waterborne polyurethane, magnesium chloride and calcium hydroxide is 30:25:1. The sulfonic acid type waterborne polyurethane is PU2695. The flow rate of the carbon dioxide gas introduced into the container is 300mL / min.
[0054] Example 4
[0055] The difference between Example 4 and Example 1 is that the curing temperature in step S2 of Example 4 is 150°C.
[0056] Example 5
[0057] The difference between Example 5 and Example 1 is that the curing temperature in step S2 is 160°C.
[0058] Example 6
[0059] The difference between Example 6 and Example 1 is that the curing temperature in step S2 is 175°C.
[0060] Example 7
[0061] The difference between Example 7 and Example 1 is that the curing temperature in step S2 is 180°C.
[0062] Example 8
[0063] The difference between Example 8 and Example 1 is that the mass ratio of sulfonic acid type waterborne polyurethane, magnesium chloride and calcium hydroxide is 23:23:1.
[0064] Example 9
[0065] The difference between Example 9 and Example 1 is that the mass ratio of sulfonic acid type waterborne polyurethane, magnesium chloride and calcium hydroxide is 27:20:1.
[0066] Example 10
[0067] The difference between Example 10 and Example 1 is that the mass ratio of sulfonic acid type waterborne polyurethane, magnesium chloride and calcium hydroxide is 30:25:1.
[0068] Embodiment 11
[0069] The difference between Example 11 and Example 1 is that: in step S1, polyester yarn is selected as the warp yarn, and the warp density is 210 yarns / inch; linen yarn is selected as the weft yarn, and the weft density is 185 yarns / inch.
[0070] Example 12
[0071] The difference between Example 12 and Example 1 is that the composite base fabric is immersed in the first finishing agent, the composite base fabric is taken out, and directly cured without drying.
[0072] Embodiment 13
[0073] The difference between Example 13 and Example 1 is that the pH value of the first finishing agent is 2.
[0074] Embodiment 14
[0075] The difference between Example 14 and Example 1 is that the pH value of the first finishing agent is 4.
[0076] Embodiment 15
[0077] The difference between Example 15 and Example 1 is that the pH value of the first finishing agent is 6.
[0078] Comparative Example 1
[0079] The difference between Comparative Example 1 and Example 1 is that the base fabric of Comparative Example 1 is not treated with the first finishing agent and the second finishing agent.
[0080] Comparative Example 2
[0081] The difference between Comparative Example 2 and Example 1 is that the base fabric of Comparative Example 2 is only treated with the first finishing agent but not with the second finishing agent.
[0082] Comparative Example 3
[0083] The difference between Comparative Example 3 and Example 1 is that the base fabric of Comparative Example 3 is only treated with the second finishing agent but not with the first finishing agent.
[0084] Comparative Example 4
[0085] The difference between Comparative Example 4 and Example 1 is that the pH value of the first finishing agent is 7.
[0086] Comparative Example 5
[0087] The difference between Comparative Example 5 and Example 1 is that pyromellitic acid is replaced by 1,2,3,4-butanetetracarboxylic acid.
[0088] Comparative Example 6
[0089] The difference between Comparative Example 6 and Example 1 is that no polyurethane is added to the second finishing agent.
[0090] Comparative Example 7
[0091] The difference between Comparative Example 7 and Example 1 is that magnesium chloride is not added to the second finishing agent.
[0092] Comparative Example 8
[0093] The difference between Comparative Example 8 and Example 1 is that no calcium hydroxide is added to the second finishing agent.
[0094] Comparative Example 9
[0095] The difference between Comparative Example 9 and Example 1 is that the mass ratio of the sulfonic acid type waterborne polyurethane, magnesium chloride and calcium hydroxide in the second finishing agent is 31:18:1.
[0096] Comparative Example 10
[0097] The difference between Comparative Example 10 and Example 1 is that the mass density of the second finishing agent is 95 g·m -2 .
[0098] Comparative Example 11
[0099] The difference between Comparative Example 11 and Example 1 is that the mass density of the second finishing agent is 205 g·m -2 .
[0100] Comparative Example 12
[0101] The difference between Comparative Example 12 and Example 1 is that carboxylic acid type waterborne polyurethane is selected to replace sulfonic acid type waterborne polyurethane.
[0102] Performance Testing
[0103] The woven fabrics of Examples 1 to 15 and Comparative Examples 1 to 12 were tested as follows:
[0104] 1. Wrinkle Recovery Angle (WRA)
[0105] Refer to GB / T 3819-1997 "Determination of Crease Recovery of Textile Fabrics - Recovery Angle Method", use a fabric crease recovery tester, take 5 samples in each direction of warp and weft, adjust humidity in a standard atmospheric balance box for 24 hours, and then test and take the average values in warp and weft respectively. The sum of the warp and weft average values is used as the fabric wrinkle recovery index. See Table 1 for specific data.
[0106] 2. Breaking strength
[0107] Refer to GB / T 3923.1-2013 "Tensile properties of textile fabrics Part 1: Determination of breaking strength and elongation at break (strip method)" and use an electronic fabric strength tester. During the operation, cut 5 samples with a length of 30 cm in the weft direction and 6 cm in the warp direction, extract the yarn edge to 5 cm along the warp direction, place it in a standard atmospheric balance box for 24 hours, and then measure its breaking strength and calculate the average value (gauge: 20 cm, tensile speed: 100 mm / min, recovery speed: 300 mm / min). It should be noted that the breaking strength of the yarn that breaks first is tested. See Table 1 for specific data.
[0108] 3. Air permeability
[0109] According to GB / T 5453-1997 "Determination of Air Permeability of Textile Fabrics", the air permeability of fabrics was measured using the YG461E-III fully automatic air permeability meter. Specific data are shown in Table 1.
[0110] Table 1 Performance data of each group of woven fabrics
[0111]
[0112]
[0113] As shown in Table 1, Examples 1, 4 to 7 are to explore the effect of the curing temperature of the first finishing agent on the performance of the woven fabric. Combined with the data trend, it can be seen that the curing temperature is better when it is 160-175°C, and the optimal temperature is 170°C. When it exceeds 170°C, there may be excessive cross-linking, which has limited improvement in anti-wrinkle performance and affects the air permeability; when it is lower than 160°C, the esterification reaction is incomplete, and the product cannot be stably cross-linked on the surface of the flax fiber, thereby significantly reducing the wrinkle resistance, mechanical properties and air permeability. Therefore, within the temperature range of 160-175°C, pyromellitic acid and the fibers in the flax can undergo an esterification reaction, which can produce a relatively stable uniform cross-linked network, thereby improving the anti-wrinkle performance and breaking strength of the flax.
[0114] Examples 1, 8 to 10 and Comparative Example 9 are mainly intended to explore the effect of the mass ratio of sulfonic acid waterborne polyurethane, magnesium chloride and calcium hydroxide in the second finishing agent on the performance of the woven fabric. Combined with the data, it can be seen that when the mass ratio of sulfonic acid waterborne polyurethane, magnesium chloride and calcium hydroxide is in the range of (20 to 30): (20 to 25): 1, the wrinkle resistance and air permeability of the woven fabric can be improved.
[0115] The difference between Example 1 and Example 11 is only the selection of warp and weft yarns. Their air permeability and wrinkle resistance are not much different. However, since the breaking strength is mainly to detect the yarn that breaks first, the radial breaking strength of the fabric is generally higher than the weft strength, so the weft yarn is generally easy to break. Example 1 uses relatively high strength and strong polyester, while Example 11 uses flax as the weft yarn, which has a significantly lower strength than polyester. Therefore, in actual production, it is preferred to use polyester as the weft yarn and flax as the warp yarn, which can take into account wrinkle resistance, mechanical strength and air permeability at the same time.
[0116] The difference between Example 1 and Example 12 is that in step S2 of Example 1, before the composite base fabric is immersed in the first finishing agent and taken out for curing, there is an additional drying step. The various properties of the woven fabric of Example 1 are better than those of Example 12. This is because the solvent of pyromellitic acid in the first finishing agent is ethanol. If curing is performed directly, ethanol may affect the subsequent curing process, thereby affecting the adhesion effect of the finishing agent on the fabric and reducing the wrinkle resistance and air permeability. Therefore, drying the base fabric before curing can effectively remove impurities such as ethanol, make the fabric surface purer, and facilitate the full combination of the first finishing agent and the fabric.
[0117] Example 1, Examples 13 to 15 and Comparative Example 4 are intended to explore the effect of pH in the first finishing agent on the performance of the woven fabric. Acidic conditions help promote the esterification reaction because the acid can act as a proton source to promote the protonation of the hydroxyl group, thereby facilitating the attack of the nucleophilic agent hypophosphite on the carbonyl carbon. The pH of Comparative Example 4 is 7. Under neutral conditions, the esterification reaction efficiency of sodium hypophosphite and pyromellitic acid is low, and the cross-linking network is significantly reduced, so the wrinkle resistance and mechanical strength of the woven fabric are also significantly reduced. When the pH is in the range of 2 to 3, the performance of the woven fabric is better, because strong acid conditions are conducive to improving the ionization and catalytic activity of sodium hypophosphite, and also promote the activity of the carboxyl group in the polycarboxylic acid and the entire esterification reaction.
[0118] The woven fabric of comparative example 1 is not treated with the first finishing agent and the second finishing agent, while comparative examples 2 and 3 are only treated with the first finishing agent or the second finishing agent. The air permeability of the woven fabric is higher than that of example 1, indicating that the first finishing agent and the second finishing agent will affect the air permeability of the woven fabric to a certain extent. Compared with comparative examples 1 to 3, the air permeability of example 1 is reduced by 2.6%, 1.4% and 1.6%, respectively. However, the wrinkle resistance of example 1 is improved by 24.4%, 15.6% and 14.5% compared with comparative examples 1 to 3, respectively, and the breaking strength is improved by 17.5%, 15.3% and 14.8% compared with comparative examples 1 to 3, respectively. Therefore, the first finishing agent and the second finishing agent selected in the present invention significantly improve the wrinkle recovery angle and breaking strength of the woven fabric, while having little effect on the air permeability, so that the woven fabric can take into account the wrinkle resistance, mechanical strength and air permeability at the same time.
[0119] Comparative Example 5 uses 1,2,3,4-butanetetracarboxylic acid to replace pyromellitic acid. Its wrinkle recovery angle is similar to that of Example 1, but its breaking strength and air permeability are significantly lower than those of Example 1. Because pyromellitic acid is an aromatic carboxylic acid, its esterification catalytic effect is lower than that of aliphatic carboxylic acids (such as 1,2,3,4-butanetetracarboxylic acid and citric acid), it can reduce the damage of the macromolecular chain in the flax fiber and reduce the strength loss of the fiber, thereby maintaining good mechanical strength and air permeability.
[0120] In Comparative Example 6, no polyurethane is added, and its air permeability is increased, but the wrinkle resistance and mechanical strength are significantly reduced, indicating that the isocyanate group (-NCO) in the polyurethane resin can react with the hydroxyl group in the cellulose fiber to form covalent crosslinks, thereby improving the wrinkle resistance and dimensional stability of the fabric.
[0121] In Comparative Example 7, magnesium chloride is not added. Similarly, its air permeability is increased, while its anti-wrinkle performance and mechanical strength are significantly decreased. Magnesium chloride helps to enhance the stability of calcium carbonate because Mg 2+ Ions can bind to CO3 on the surface of CaCO3 2- Ions undergo ion exchange, thereby improving the dispersion and stability of calcium carbonate in the base fabric. At the same time, magnesium chloride is also used as a catalyst to accelerate the cross-linking reaction between polyurethane resin and fiber, shorten the curing time, and improve finishing efficiency.
[0122] In Comparative Example 8, no calcium hydroxide is added, that is, calcium carbonate cannot be synthesized in situ. Calcium carbonate can fill the gaps in the flax fibers, thereby significantly improving the anti-wrinkle effect and mechanical strength of the base fabric, but it will also affect the air permeability.
[0123] Comparative Examples 10 and 11 are respectively the second finishing agent having a mass density not in the range of 100 to 200 g·m -2In the range of 10 to 200 g·m2, the amount of the second finishing agent added in Comparative Example 10 is too low, and the air permeability is improved compared with Example 1, but the anti-wrinkle performance and mechanical strength are significantly reduced; the amount of the second finishing agent added in Comparative Example 11 is too high, and the anti-wrinkle performance and mechanical strength are not much different from those in Example 1, but the air permeability is significantly reduced. Therefore, the mass density of the second finishing agent selected in the present invention is 100 to 200 g·m2. -2 .
[0124] Comparative Example 12 uses carboxylic acid type waterborne polyurethane, because the pH of the first finishing agent is 2-6, carboxylic acid is easily formed at low pH value, resulting in reduced hydrophilicity, thus affecting the stability of the emulsion, so its anti-wrinkle performance and mechanical strength are significantly lower than those of Example 1. Therefore, the present invention uses sulfonic acid type waterborne polyurethane as the finishing agent, because its hydrophilic group is sulfonic acid group (-SO3H), which can maintain good stability and hydrophilicity even at a lower pH value, so sulfonic acid type WPU usually has a wider pH stability range.
[0125] In summary, the woven fabric obtained by the preparation method of the present invention has good wrinkle resistance, air permeability and wear resistance. Figure 1 As shown, the woven cloth can be used to prepare clothes and decorative materials.
[0126] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing an environmentally friendly wrinkle-resistant woven fabric, characterized in that: The following steps are involved: S1. Using polyester yarn and linen yarn as warp yarn and / or weft yarn respectively, and weaving the warp yarn and weft yarn perpendicular to each other to obtain a composite base fabric; S2, immersing the composite base fabric in a first finishing agent, taking out the composite base fabric and curing it, washing and drying it after curing to obtain an esterified base fabric; wherein the first finishing agent is an ethanol solution of sodium hypophosphite and pyromellitic acid, with a pH of 2 to 6; the mass density of the first finishing agent is 400 to 600 g·m- 2 The sodium hypophosphite and pyromellitic acid account for 70-80wt% of the total mass of the first finishing agent, the mass ratio of sodium hypophosphite to pyromellitic acid is (0.5-1):1 in molar ratio, the curing temperature is 150-180°C, and the curing time is 30-120s; S 3. Immerse the esterified base fabric in a second finishing agent, which is a mixed solution of sulfonic acid type waterborne polyurethane, magnesium chloride and calcium hydroxide, and then place the base fabric in a container filled with carbon dioxide gas, and continue to introduce carbon dioxide gas into the container for an in-situ synthesis reaction for 15 to 30 minutes, so that calcium hydroxide reacts with carbon dioxide to generate calcium carbonate. After the reaction, take out the base fabric, dry it, and then wash it. After drying, the environmentally friendly wrinkle-resistant woven fabric is obtained; wherein the mass density of the second finishing agent is 100 to 200 g·m- 2 ; The sulfonic acid type water-based polyurethane, magnesium chloride and calcium hydroxide account for 60-70wt% of the total mass of the second finishing agent, and the mass ratio of the sulfonic acid type water-based polyurethane, magnesium chloride and calcium hydroxide is (20-30): (20-25): 1; the flow rate of the carbon dioxide gas introduced into the container is 200-300mL / min.
2. The method for preparing the environmentally friendly wrinkle-resistant woven fabric according to claim 1, characterized in that: In the step S1, the flax yarn is the warp yarn, and the density in the warp direction is 200 to 250 yarns / inch; the polyester yarn is the weft yarn, and the density in the weft direction is 150 to 200 yarns / inch.
3. The method for preparing the environmentally friendly wrinkle-resistant woven fabric according to claim 1, characterized in that: In the step S2, the curing temperature is 160-175° C. and the curing time is 60-90 seconds.
4. The method for preparing the environmentally friendly wrinkle-resistant woven fabric according to claim 1, characterized in that: In the step S2, the composite base fabric is immersed in a first finishing agent, the composite base fabric is taken out, dried and then cured; the drying temperature is 90-100° C. and the drying time is 1-5 minutes.
5. The method for preparing the environmentally friendly wrinkle-resistant woven fabric according to claim 1, characterized in that: The sulfonic acid type waterborne polyurethane is at least one of PU2650, PU2660, PU2690 and PU2695.
6. The method for preparing the environmentally friendly wrinkle-resistant woven fabric according to claim 1, characterized in that: In step S3, the flow rate of the carbon dioxide gas introduced into the container is 250-300 mL / min.
7. The method for preparing the environmentally friendly wrinkle-resistant woven fabric according to claim 1, characterized in that: In step S3, the drying temperature is 50-70° C. and the drying time is 5-10 minutes.
8. The method for preparing the environmentally friendly wrinkle-resistant woven fabric according to claim 1, characterized in that: In the step S3, the mass ratio of the sulfonic acid type waterborne polyurethane to the magnesium chloride is (1.15-1.2):
1.
9. An environmentally friendly wrinkle-resistant woven fabric, characterized in that: The environmentally friendly anti-wrinkle woven fabric is prepared by the preparation method of any one of claims 1 to 8.
10. Use of an environmentally friendly wrinkle-resistant woven fabric in the preparation of decorative materials and / or clothing.
Citation Information
Patent Citations
Catalysts and processes for formaldehyde-free durable press finishing of cotton textiles with polycarboxylic acids
CN1039456A
Crease-resistance fabric
CN108374285A
Long-acting dry antibacterial polyester fabric and preparation method thereof
CN117802624A